The Social Turn in SLA: An Analysis of the Cognitive and Socio-Cultural Dimensions of L2 Learners’ Interactions - Rosique-Martínez, Luis Alberto; Izquierdo, Jesús (Cinzontle, 2018)
The Social Turn in Second Language Acquisition (SLA) addresses the importance of social context in language development. Building upon this theoretical strand, this small-scale research examines the dyadic interaction of university Mexican learners of English in a problem-solving task through a socio-cultural model of analysis. The interactional analysis of learner performance revealed that, along with linguistic attention, ideology, identity and affective scaffolding arose during the information exchange. In line with claims from the socio-cultural strand of SLA, we argue that these features created interactional conditions that allowed for successful communication in the target language and task completion.